2014
DOI: 10.1109/access.2014.2362522
|View full text |Cite
|
Sign up to set email alerts
|

Information Security in Big Data: Privacy and Data Mining

Abstract: The growing popularity and development of data mining technologies bring serious threat to the security of individual's sensitive information. An emerging research topic in data mining, known as privacypreserving data mining (PPDM), has been extensively studied in recent years. The basic idea of PPDM is to modify the data in such a way so as to perform data mining algorithms effectively without compromising the security of sensitive information contained in the data. Current studies of PPDM mainly focus on how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(68 citation statements)
references
References 102 publications
0
62
0
6
Order By: Relevance
“…This lifecycle model is continually being improved with emphasis on constant attention and continual monitoring [21]. In this paper, we suggest a model that combines the phases presented in [20] and phases mentioned in [21], in order to provide encompass policies and mechanisms that ensure addressing threats and attacks in each step of big data life cycle. Figure 1 presents the main elements in big data lifecycle in healthcare.…”
Section: A Big Data Security Lifecyclementioning
confidence: 99%
See 2 more Smart Citations
“…This lifecycle model is continually being improved with emphasis on constant attention and continual monitoring [21]. In this paper, we suggest a model that combines the phases presented in [20] and phases mentioned in [21], in order to provide encompass policies and mechanisms that ensure addressing threats and attacks in each step of big data life cycle. Figure 1 presents the main elements in big data lifecycle in healthcare.…”
Section: A Big Data Security Lifecyclementioning
confidence: 99%
“…Yazan et al [20] suggested a big data security lifecycle model extended from Xu et al [21]. This model is designed to address the phases of the big data lifecycle and correlate threats and attacks that face big data environment within these phases, while [21] address big data lifecycle from user role perspective: data provider, data collector, data miner, and decision maker.…”
Section: A Big Data Security Lifecyclementioning
confidence: 99%
See 1 more Smart Citation
“…The privacy issues are viewed in a wider perspective when it relates to data mining and considers various approaches to protect sensitive information [19]. A new knowledge can be extracted through data analytics and aggregated through data processing but not lead to privacy issues of a user [14].…”
Section: A Privacy Issuesmentioning
confidence: 99%
“…Data provenance in big data has been explored recently but it has been studied in database and distributed systems communitie's. It simply refers to the ownership of data or custodian of data and the location of the data where it resides [19]. It is a process of maintaining the origin and creation of data which is useful for validating the data, determining the reliability of data and evaluating the quality of data.…”
Section: B Data Provenance Problemmentioning
confidence: 99%